Observing children [videorecording] (Meridian Education Corp., 1991)
Discusses how children of a different ages and abilities reveal a great deal about their developmental level and readiness to learn as we see them interacting with their environment and those people in it. Suggestion for record keeping and charting observations for children file are explored to promote cooperation and understanding between parents and care givers. Examines the importance of observing children to ensure they are developing properly both physically and emotionally as well as watching for signs that reveal a child to be a victim of abuse.